Suicides During the Pandemic: A Retrospective Study - YN Singha; Arpan Mazumder; G Das (Indian Journal of Forensic Medicine & Toxicology, 2022)
Suicide is defined as a fatal self-injurious act with some evidence of intent to die.1 Suicide occurs more often inolder than in younger people, but is still one of the leading causes of death in the late childhood and adolescence.Every year, more than 1,00,000 people commit suicide in our country.1 Suicide accounts for 1.4% of all deaths,and is the 15th leading cause of death globally.2,3 Suicide is associated with an impulsive nature. Several riskfactors concerning family structure and interactions have been linked to a suicidal behaviour. Direct conflictswith parents and siblings, Occupational status and social acceptance have a great impact, but so do the absence ofcommunication and a lack of empathy.12 Interpersonal losses are also strongly associated with suicide cases. Butin developing countries one of the major reason always remains unemployment and poverty. There are differentrates of suicides and suicidal behaviour between males and females (among both adults and adolescents). Whilefemales more often have suicidal thoughts, males die by suicide more frequently.5 Hence, this study was plannedwith a purpose to know the magnitude and the socio-cultural factors of the problem of suicides, so that a soundprevention program could be suggested, planned and implemented for reducing the incidence of suicides.